A dimensão pública da arquitetura em museus: uma análise de projetos contemporâneos - Paula Zasnicoff Duarte Cardoso da Silva (2007)
This dissertation presents a study of the public dimension of contemporary museum architecture based on the analysis of three projects: the Pinacoteca do Estado de São Paulo (1993-1998), by Paulo Mendes da Rocha, the Fundação Iberê Camargo (1998-2007), in Porto Alegre, by Álvaro Siza and the 21st Century Museum of Art, Kanazawa (1999-2004), in Japan, by Kazuyo Sejima and Ryue Nishizawa. This research presents a discourse on the interface between architecture,art and education. It investigates the ways in which architecture might be used to maximise the potential of the contemporary museum. To put the theme into context, the study begins with a review of the historical and spatial evolution of the museums, moving on to an analysis of the contemporary projects. The method used divides the analysis into two parts. The first is documentary in character and evaluates each project in terms of four aspects: the institution, the architect, the site and the building. The second part is critical in character and evaluates the public dimension of the projects in question using the following guidelines: projects of action, urban concept, monumentality and relevance to the brief. The work is concluded by a reflexion on the public dimension of architecture and its evolution from modernism to contemporary architecture which seeks to create parameters for future projects.